Farewell to the poets of spinning in the Umayyad era Omar bin Abi Rabia and Jamil bin Muammar by choice (Journal of the College of Basic Education, 2023)
Praise be to God, Lord of the worlds, and prayers and peace be upon Muhammad and his family and companions altogether, and after:At the beginning of talking about the subject of this research, I have to say through it that farewell, in addition to being a prominent phenomenon in the poetry of ghazals in the Umayyad era, however, at the same time it became a precautionary position that the person of that era was forced to take, when he felt or imagined that something threatened or It lacks its entity, and from here and in view of this saying, I cannot count the farewell to the poets of the Umayyad courtship as a secretion of my life of luxury and well-being that they live, but it has become an urgent necessity that derives its meaning and its becoming from the nature of the depositor himself in particular and from the nature of the general situation that he worked to create in a more general way.